2023
DOI: 10.3390/ph16071049
|View full text |Cite
|
Sign up to set email alerts
|

The Skin and Natural Cannabinoids–Topical and Transdermal Applications

Silviu-Iulian Filipiuc,
Anca-Narcisa Neagu,
Cristina Mariana Uritu
et al.

Abstract: The chemical constituents of the Cannabis plant known as cannabinoids have been extensively researched for their potential therapeutic benefits. The use of cannabinoids applied to the skin as a potential method for both skin-related benefits and systemic administration has attracted increasing interest in recent years. This review aims to present an overview of the most recent scientific research on cannabinoids used topically, including their potential advantages for treating a number of skin conditions like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 203 publications
0
2
0
Order By: Relevance
“…The therapeutic potential of the cannabinoid CBD has been particularly researched and studied as it is abundant in the cannabis plant and has a relatively favourable legal status compared to THC. Recently, extensive review articles have been published on the therapeutic potential of phytocannabinoids, particularly cannabidiol, focusing on its effect on skin health, disease (Baswan et al, 2020;Martins et al, 2022) and delivery mechanisms (Filipiuc et al, 2023). Natural cannabinoids, including CBD, have been shown to have a positive effect in the treatment of many skin diseases (Baswan et al, 2020).…”
Section: Cannabis Extracts and Cannabinoids For The Treatment Of Skin...mentioning
confidence: 99%
“…The therapeutic potential of the cannabinoid CBD has been particularly researched and studied as it is abundant in the cannabis plant and has a relatively favourable legal status compared to THC. Recently, extensive review articles have been published on the therapeutic potential of phytocannabinoids, particularly cannabidiol, focusing on its effect on skin health, disease (Baswan et al, 2020;Martins et al, 2022) and delivery mechanisms (Filipiuc et al, 2023). Natural cannabinoids, including CBD, have been shown to have a positive effect in the treatment of many skin diseases (Baswan et al, 2020).…”
Section: Cannabis Extracts and Cannabinoids For The Treatment Of Skin...mentioning
confidence: 99%
“…Generally, environmental xenobiotics enter the human body through different absorption surfaces/barriers from input compartments: skin and its appendages, by topical application and absorption, gastro-intestinal mucosa, by ingestion and absorption, and the pulmonary alveolar–capillary membrane, by inhalation. To begin with, EDCs from personal care products are easily absorbed by the skin into systemic circulation after topical application, and can be detected in blood, urine, and breast milk [ 86 , 87 ]. However, Rylander et al (2019) concluded that intensive use of skin care products did not increase the BCR [ 86 ].…”
Section: Absorption Distribution Metabolism/biotransformation Bioaccu...mentioning
confidence: 99%

Breast Cancer Exposomics

Neagu,
Jayaweera,
Corrice
et al. 2024
Life
Self Cite
“…ECS regulates cell growth and differentiation as well as immune and inflammatory responses (Table 2). The endocannabinoids produced in the skin, N-arachidonoyletahnolamine (AEA) and 2-arachidonoylglycerol (2-AG), are binding to the main endocannabinoid receptors CB1 and CB2, as well as other receptors-TRPV1 belonging to Transient Receptor Potential (TRP) channels and PPARγ and PPARα from the Proliferator-Activated Receptors (PPAR) family [3,9]. Anti-inflammatory activity by inhibition of macrophage-1 polarization…”
Section: Skin Endocannabinoid Systemmentioning
confidence: 99%